Recurrent pericardial effusion due to Hennekam lymphangiectasia-lymphedema syndrome: a case report and literature review - Ran Zhang; Junyan Zhang; Li Rao; Zhongxiu Chen; Mian Wang (BMC Cardiovascular Disorders)
Abstract Diagnosing and treating recurrent pericardial effusion (PE) have been challenging in clinical practice. This study presents a middle-aged male with long-term refractory PE without apparent cause and non-specific symptoms, and eventually diagnosed as Hennekam lymphangiectasia with lymphedema syndrome (HKLLS). He underwent anti-tuberculosis diagnostic treatment and non-steroidal anti-inflammatory drugs for nonspecific PE, and thoracic duct exploration, terminal adhesion lysis, and anastomosis of the tributary vertebral vein of the thoracic duct for suspected protein-losing enteropathy and intestinal lymphangiectasia in other hospitals 17 and 11 years ago, but with no satisfactory outcomes. During the disease course, laboratory tests showed decreased blood albumin and increased stool α1-antitrypsin, while endoscopy biopsies were normal. The patient’s complex medical history underscores the diagnostic challenges. The whole-exome sequencing identified two mutations within the collagen and calcium-binding EGF-like domain-containing protein 1 (CCBE1) gene, diagnosing HKLLS type 1. This case enriches the understanding of the link between HKLLS and recurrent PE, highlighting the significance of whole-exome sequencing in diagnosing recurrent PE when traditional methods fall short. It also reminds clinicians to consider rare genetic disorders like HKLLS in the differential diagnosis of recurrent PE, even without typical symptoms.